PENGEMBANGAN MEDIA BOARD GAME HOMPIMPA PADA IPAS SIFAT CAHAYA KELAS V SEKOLAH DASAR - Ardianzah, Dedy; Faradita, Meirza Nanda; Martati, Badruli (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to: 1) describe the feasibility of the Hompimpa board game media in the IPAS subject on the topic of light properties for Grade V students in elementary school; and 2) describe students’ understanding and activeness in learning IPAS using the Hompimpa board game media. The researcher used the Research and Development (R&D) method, based on the 4-D model (Define, Design, Develop, and Disseminate). Data analysis techniques included questionnaires and tests. The research instruments used in this process included media expert assessment sheets, material expert sheets, teacher responses, student responses, and assessments after using the developed media. The results showed that the media expert gave a final average score of 71 with a percentage of 95%, categorized as very valid. The material expert gave a final average score of 72 with a percentage of 96%, also categorized as very valid. Teacher responses reached an average score of 44 with a percentage of 88%, categorized as very practical, while student responses reached 92%, also categorized as very practical. Student test results after using the media showed a percentage of 89%, categorized as very effective. Based on these findings, it can be concluded that the development of the Hompimpa board game media for the IPAS topic on light properties is valid, practical, and effective.